Proposed Marketing Mix to Increase Sales of Kliknik Stores in E-Commerce - Kevin Handika, Natanael; Susanto, Sani; Rian Praktikto, Fransiscus (Ann Publisher, 2024)
Kliknik is a shop that sells medicines and vitamins. Kliknik operates on e-commerce at Tokopedia and Shopee. Kliknik's main problem is not achieving the target since March 2022. This is in line with the improving pandemic conditions in Indonesia. Compared with several pharmaceutical companies' net sales, the improving pandemic conditions do not affect a company's sales. It is necessary to propose a marketing mix that Kliknik can implement based on segmenting, targeting, and positioning analysis to achieve the specified Kliknik sales target. Data collection was carried out using a questionnaire. 97 respondent data was obtained, which could be analyzed. Segmentation analysis was done by using k-means clustering. Three clusters were obtained: general, loyal, and critical customers. Through a targeting process, loyal customers were selected as the target market for Kliknik Shop. The positioning statement for the Kliknik Shop is that loyal customers can always shop at the Kliknik because the Kliknik Shop appreciates the trust they have been given. The marketing mix proposal is general but still adheres to the 4P+2P+2C+3S marketing mix concept. The proposed marketing mix given is that Kliknik Shop can take part in some events held by e-commerce, Kliknik Shop admin can actively contact customers who have finished shopping via the chat feature in e-commerce and must be responsive to respond to all chats, comments, and discussions. Kliknik shops are also advised to create social media, Instagram, as a promotional media and extend store operating hours.